Design of a prodrug bispecific antibody masked by a functional molecule for lymphocyte activation for cancer therapy - Daimei Miura; Yuki Kato; Masahiro Yasunaga; Izumi Kumagai; Ryutaro Asano (Journal of Biological Engineering)
Abstract Although T cells engaging bispecific antibodies (T-bsAbs) have shown great benefits, their use in treating solid tumors is challenging because of the minimal infiltration of T-cells. We fused an agonistic single-chain variable fragment (scFv) that induces a T cell co-stimulatory signal to the T cell-binding domain of T-bsAb via a linker containing a cancer-specific protease recognition site. With this antibody format, unexpected cytotoxicity to the surrounding normal tissue would be reduced and tumor-specific T cell activation would occur. The scFv-masked T-bsAb was cleaved by collagenase with intrinsic cancer-specific protease activity, releasing agonistic scFv without unwanted fragmentation and restoring the binding ability of the scFv-masked bsAbs to T cells. Compared to the original bsAb, a detectable enhancement of the T cell proliferation and cancer cytotoxicity was observed after the incubation with collagenase or protease-secretory cancer cells, which was suggested to be due to the modest co-stimulation by the released agonistic scFv. Our results provide important insights into an ideal T-bsAb prodrug format, precisely engineered to reduce side effects and exert high cancer cytotoxicity for solid tumor precision medicine.